PERBEDAAN PELAYANAN PERSALINAN BIDAN DAN DUKUN DARI SUDUT PANDANG PASIEN DIDUSUN DADAPAN PUSKESMAS ANDONGSARI - Yuliani, Ida; Setyowati, Lisus; Rohmatin, Homsiatur (Jurnal Sains, Teknologi dan Kesehatan, 2023)
Delivery assistance by health workers is a strategy to deal with maternal and child health problems in Indonesia. The ability and skills of birth attendants greatly affect the occurrence of maternal and infant mortality. This study aims to determine the differences in the delivery services of midwives and shamans from the patient's point of view in the Dadapan hamlet of Andongsari Health Center in 2022. This research design uses a qualitative approach and includes a comparative study research. The sample in this study as many as 16 respondents by using snowball sampling technique. From the results of the study, it was found that patients prefer delivery at midwives because the quality aspects offered by midwives are superior, ranging from assurance, responsiveness, empathy to physical evidence. This aspect is created from the education and experience gained by midwives when they were in college and the practical experience that has been carried out. From the patient's point of view, ease of access is superior to shamans, because there are more dukuns than midwives. In this study, patients who were interviewed had closer access to traditional healers than midwives.